FAKTOR KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN SUMBAWA - Rachman, Rosyidah; Mergiansyah, M (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to know the effect of communication, motivation, and work environment in improving the performance of employees at Community and Village Empowerment Office of Sumbawa District. This type of research is associative research which is used to determine the direction and extent of influence of communication factors (X1), motivation (X2), and work environment (X3) on the performance of employees at Community and Village Empowerment Office of Sumbawa District (Y). The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The population in this study were all employees at Community and Village Empowerment Office of Sumbawa District, totaling 33 people. All members of the population totaling 33 people will be used as research samples so that this study is categorized as population research. Data analysis tools were performed using multiple linear regression analysis techniques, t test, F test, and the coefficient of determination (R2) test. The results of this study showed that communication, motivation and work environment had a positive and significant effect on the employees’ performance at Community and Village Empowerment Office of Sumbawa District, both partially and simultaneously. The contribution of communication, motivation and work environment variables in influencing changes on employees’ performance at Community and Village Empowerment Office of Sumbawa District was 80.4%, while the remaining of 19.6% was effected by other variables outside this research model, such as wages, job security, working conditions, achievements, training and work experience.